Political Participation in the Context of Platformization: A Technological Affordances Perspective - Auškalnienė, Lina (Information & Media, 2025)
Introduction. Social media has become a key space where political participation is shaped and mediated in contemporary societies. Although widely researched over the past decade, practices in the evolving digital sphere still require deeper understanding. The paper explores how technological affordances – visibility, persistence, editability, and association (Treem & Leonardi, 2013) – not only enable but also constrain civic engagement. Methods. By using a qualitative research paradigm (focus groups), the paper examines both technological and subjective aspects of political participation. The research question is: How do social media affordances enable and constrain citizens’ online political participation in Lithuania? Analysis and results. The findings reveal that, although technological affordances expand access to political information and enable expression, this empowerment remains uneven and limited. Participants describe tensions related to algorithmic filtering, self-censorship, and low self-efficacy, which lead to a passive and observational mode of participation. Conclusions. While platforms promise empowerment, political participation remains shaped by algorithmic filtering and social dynamics that often discourage deeper engagement. In this way, technological affordances both enable and constrain participation in an ongoing, dynamic process, where digital tools and citizens’ agency continually interact.